Neural Responses during Social and Self-Knowledge Tasks in Bulimia Nervosa - Mcadams, Carrie J.; Krawczyk, Daniel C. (Frontiers in Psychiatry, 2013)
Self-evaluation closely dependent upon body shape and weight is one of the defining criteria for bulimia nervosa. We studied 53 adult women, 17 with bulimia nervosa, 18 with a recent history of anorexia nervosa, and 18 healthy comparison women, using three different fMRI tasks that required thinking about self-knowledge and social interactions: the Social Identity task, the Physical Identity task, and the Social Attribution task. Previously, we identified regions of interest (ROI) in the same tasks using whole brain voxel-wise comparisons of the healthy comparison women and women with a recent history of anorexia nervosa. Here, we report on the neural activations in those ROIs in subjects with bulimia nervosa. In the Social Attribution task, we examined activity in the right temporoparietal junction, an area frequently associated with mentalization. In the Social Identity task, we examined activity in the precuneus and dorsal anterior cingulate. In the Physical Identity task, we examined activity in a ventral region of the dorsal anterior cingulate. Interestingly, in all tested regions, the average activation in subjects with bulimia was more than the average activation levels seen in the subjects with a history of anorexia but less than that seen in healthy subjects. In three regions, the right temporoparietal junction, the precuneus, and the dorsal anterior cingulate, group responses in the subjects with bulimia were significantly different from healthy subjects but not subjects with anorexia. The neural activations of people with bulimia nervosa performing fMRI tasks engaging social processing are more similar to people with anorexia nervosa than healthy people. This suggests biological measures of social processes may be helpful in characterizing individuals with eating disorders.